Applying multi-response optimization for sustainable machining of 316 stainless steel with coconut oil-assisted minimum quantity lubrication. (2nd January 2023) - Kadi, Rajendrakumar V.; Dundur, Suresh T.; Goudar, Dayanand M.; Haider, Julfikar
ABSTRACT: Environmental machining was investigated using coconut oil and minimal quantity lubrication (MQL) in the turning of AISI 316 stainless steel. The turning parameters and MQL flow rate were optimized using ANOM and ANOVA in multi-response analysis to obtain the best hardness and minimum surface roughness. The feed, speed, depth of cut, and MQL flow rate were used as input parameters. It was observed that minimum surface roughness ( R a : 1.12 μm and R z : 6.37 μm) at cutting speed of 120 m/min, feed rate between 0.25 and 0.3 mm/rev, the depth of cut between 1.0 and 1.5 mm and a flow rate of 90 ml/h. The high hardness of 230 μHv at machined surface and machining affected zone (MAZ) was observed to a depth of 1.075 mm. The coconut oil was shown to be an ecofriendly lubricant for machining difficult-to-cut materials like stainless steel and keeping good surface integrity. GRAPHICAL ABSTRACT: UF0001